Composition of Marine Debris on The Coast of Banyuwangi, East Java - Arifianti, Dwi Nurjanatin; Yona, Defri; Sari, Syarifah Hikmah Julinda (Universitas Airlangga, 2024)
Marine debris has emerged as a significant environmental issue of growing global concern, closely linked to pollution and its impact on the environment. Understanding the distribution of marine waste in coastal areas is crucial, especially considering that beaches are key sites for various human activities such as tourism, fishing, and shipping. To address this, a study was conducted to analyze the composition of marine debris on three beaches in Banyuwangi Regency, East Java. The study took place in July and August of 2023, focusing on Boom, Cacalan, and Cemara beaches. Marine debris was collected along the coastline in 5 x 5 m transects, spaced 20 m apart, to identify and quantify the types of waste. The findings revealed that Boom Beach had the highest percentage of rubbish (46%), followed by Cemara Beach (30%) and Cacalan Beach (24%). Additionally, the highest abundance of rubbish per area was found at Boom Beach (5.97 ± 16.64 item/m2), Cemara Beach (3,92 ± 11,36 item/m2), and Cacalan Beach (3,12 ± 5,27 item/m2). Boom Beach and Cemara Beach were primarily dominated by plastic waste, while at Cacalan Beach, plastic waste and broken glass were found in nearly equal proportions. The calculation of the Clean Coast Index (CCI) indicated that all three beaches were significantly polluted. As a result, there is a clear need for focused attention on waste management at tourist beaches to preserve the aesthetics and comfort of beach visitors.